2005
DOI: 10.1038/sj.bjc.6602375
|View full text |Cite
|
Sign up to set email alerts
|

17β-Hydroxysteroid dehydrogenases involved in local oestrogen synthesis have prognostic significance in breast cancer

Abstract: The 17b-hydroxysteroid dehydrogenase (17HSD) enzymes are involved in the local regulation of sex steroids. The 17HSD type 1 enzyme catalyses the interconversion of the weak oestrone (E1) to the more potent oestradiol (E2), whereas 17HSD type 2 catalyses the oxidation of E2 to E1. The aim of this study was to correlate the expression of these enzymes in the tumour with the recurrence-free survival of tamoxifen-treated breast cancer patients. We used real-time reverse transcriptase PCR to investigate the mRNA ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
86
2
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(94 citation statements)
references
References 24 publications
4
86
2
2
Order By: Relevance
“…In addition, expression of an androgen-induced gene 17bHSD2 may reflect intratumoral DHT actions in breast carcinoma more precisely than AR status. Gunnarsson et al (2005) reported a significant association between 17bHSD2 mRNA and better recurrence-free survival in the breast carcinoma. Therefore, 17bHSD2-positive breast carcinoma after a neoadjuvant aromatase inhibitor therapy possibly may grow more slowly by increased intratumoral DHT actions and/or further decreased estrogen actions by 17bHSD2 (Fig.…”
Section: K Takagi Et Al: Intratumoral Androgens In Breast Carcinomamentioning
confidence: 99%
“…In addition, expression of an androgen-induced gene 17bHSD2 may reflect intratumoral DHT actions in breast carcinoma more precisely than AR status. Gunnarsson et al (2005) reported a significant association between 17bHSD2 mRNA and better recurrence-free survival in the breast carcinoma. Therefore, 17bHSD2-positive breast carcinoma after a neoadjuvant aromatase inhibitor therapy possibly may grow more slowly by increased intratumoral DHT actions and/or further decreased estrogen actions by 17bHSD2 (Fig.…”
Section: K Takagi Et Al: Intratumoral Androgens In Breast Carcinomamentioning
confidence: 99%
“…17βHSD5 converts androstendione to testosterone and oestrone to oestradiol. We have previously shown that 17βHSD1, 17βHSD2, 17βHSD5 and 17βHSD14 are important as prognostic and treatment predictive factors in breast cancer [10][11][12][13]. It has been shown that progestins influence the oestradiol and testosterone levels, and these effects have been presumed to be an effect caused by altered regulation of 17βHSD enzymes; however the contribution of separate family members of the 17βHSD-family has not been addressed [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The potency of steroidal sex hormones like E2 is modulated by enzymes of the 17β-hydroxysteroid dehydrogenase (17β-HSD) family (Lukacik et al, 2006), especially 17β-HSD1 and 17β-HSD2, which catalyze the activation of E2 from estrone (E1) or the deactivation of E2 into E1, respectively (Chart 1). 17β-HSD1 is a cytosolic enzyme present in different organs like ovaries, placenta, breast, endometrium (Vihko et al, 2001) which is often overexpressed in breast cancer tissues (Suzuki et al, 2000;Gunnarsson et al, 2001;Miyoshi et al, 2001;Gunnarsson et al, 2005) and endometriosis (Šmuc et al, 2007). Consequently, selective inhibition of 17β-HSD1 is discussed to be a good strategy to reduce the intracellular E2 levels and regarded as a new therapeutic approach for the treatment of estrogen-dependent diseases.…”
Section: Introductionmentioning
confidence: 99%